Value Relevance of Accounting Information in Chinese Listed Companies: An empirical study based on Ohlson valuation framework - Zhang, Kai (2016)
This paper examines empirically how investors perceive the information content of accounting information under Chinese Accounting Standards for explaining stock prices over time. The study investigates the value relevance of accounting information in Chinese listed companies for the period from 2000 to 2015 based on Ohlson’s (1995) valuation framework. The results demonstrate that earnings and book value are value relevant to the pricing process in all years. Furthermore, the combined value relevance of earnings and book value does not have a temporal trend of either increase or decrease, but fluctuates substantially over time. The relative importance of earnings and book value in explaining stock price also fluctuates remarkably and exceeds each other alternately over time. Besides, negative earnings and large intangibles do not change the trend of fluctuations in the value relevance of earnings and book value, and the fluctuations are not correlated with the stock market sentiment.